Adaptation of online courses for new educational contexts - Jamie Rossiter (Athabasca University Press, 2009)
One of the challenges in online learning is adaptation of material developed for one educational setting to be appropriate in another. Qualitative case-study research explored adaptation of online continuing education modules, developed by the Public Health Agency of Canada for public health practitioners. Two adaptations were studied: the College of Medicine, University of Saskatchewan, and English-speaking Caribbean countries. The first case involved adaptation for different learners, but in a similar culture. The second case involved similar learners, but in a different culture. Results show that adaptation of existing online courses can be practicable, and may take less time and fewer resources to implement than creation of a new course. Benefits extended beyond immediate educational objectives to address strategic goals of both originating and recipient organizations.